Specific RNA sequences and gene products of MC29 avian acute leukemia virus - Mellon, Pamela (1978)
The 28S RNA of the defective avian acute leukemia virus MC29 contains two sets of sequences: 60% are hybridized by DNA complementary to other avian tumor virus RNAs (group-specific cDNA) and 40% are hybridized only by MC29-specific cDNA. Specific and group-specific sequences of viral RNA, defined in terms of their large RNase T(1)-resistant oligonucleotides, were located on a map of all large T(1) oligonucleotides of viral RNA. Oligonucleotides representing MC29-specific sequences of viral RNA mapped between 0.4 and 0.7 unit from the 3′-poly(A) end. Oligonucleotides of group-specific sequences mapped between 0 and 0.4 and between 0.7 and 1 map unit. Cell-free translation of viral RNA yielded three proteins with approximate molecular weights of 120,000, 56,000, and 37,000, termed P120(mc), P56(mc), and P37(mc). P120(mc) contained both MC29-specific peptides and serological determinants and peptides of the conserved, internal group-specific antigens of avian tumor viruses. P120(mc) is translated only from full-length 28S RNA. Furthermore, MC29 RNA contains sequences related to the group-specific antigen gene (gag), near the 5′ end, which are followed by MC29-specific sequences. We conclude that this protein is translated from the 5′ 60% of the RNA, and that it includes a segment translated from the specific sequences. It is suggested that the transforming (onc) gene of MC29 may consists of the specific and some group-specific RNA sequences and that P120(mc), which is also found in transformed cells, may be the onc gene product.